Sculptural ceramics - Gregory, Ian (A & C Books, 1992)
"In this book, Ian Gregory first sketches the history of man's clay figure work. He then provides a lot of technical information for the would-be sculptural ceramicist. He starts with the basics of clay -- which to use for the different purposes, how to modify the clay for strength and colour, and which textural techniques to use for decorating the methods of forming the clay -- coiling, casting, modelling etc. -- and decoration methods. Finally he looks at kilns -- which to use and how to build them -- as well as which fuels to use. The book is rounded off with a survey of work that is currently being done in the field. The author uses examples of work from all over the world to show just what an exciting and creative area of ceramics this is." -- Dust jacket